Implementing advance care planning in Swedish healthcare settings - a qualitative study of professionals' experiences - Simon Beck; Lina Lundblad; Camilla Göras; Malin Eneslätt (Taylor & Francis Group, 2023)
AbstractBackground Advance care planning (ACP) is a process involving conversations about values and preferences regarding future care at the end-of-life. ACP has led to positive outcomes, both in relation to quality of life and with increased use of palliative care, less life-sustaining treatment and fewer hospital admissions. Sweden has yet to embrace the practice systematically, but scattered initiatives exist.Aim To study implementation of a routine for ACP in NH settings in Sweden by exploring healthcare professionals' experiences of engaging in ACP following this implementation.Methods The study followed a qualitative inductive design with convenience and snowball sampling. Semi-structured group and individual interviews with registered healthcare professionals were analysed using qualitative content analysis.Findings Organisational support for sustainable ACP implementation was found to be essential. This included sufficient training, facilitation, collaboration and uniform work routines across providers and professionals. Engaging in ACP conversations following the implemented routine was found to be a process of preparing, being, talking, deciding and sharing.Conclusions Successful implementation of ACP in NHs requires a carefully planned implementation strategy. ACP in NHs tend to be medically focused at the expense of residents' psychosocial care-planning needs. Widespread uptake of ACP in Sweden could be useful in the national effort to adopt more person-centred care in Swedish healthcare.KEY POINTS While advance care planning has been implemented in many other countries, Sweden lacks a national strategy on advance care planning and Swedish healthcare settings have yet to systematically implement this practice.  • This study is the first to report on professionals' experiences of engaging in sustainable advance care planning, following top-down implementation of the practice in one Swedish region.  • Successful implementation of advance care planning in nursing homes requires a system-level approach, and shortcomings of the implementation process are highlighted.